Integration of rail and bicycle transport in agglomeration regions on the example of the Łódź Agglomeration Railway and the public bicycle system Rowerowe Łódzkie - Oleska, Katarzyna (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents’ Perspective, 2024)
The chapter addresses the integration of railway and bicycle transport in agglomerated regions. Integrating public bicycle systems with railways is an effective solution to improve access to railway transport and facilitate eco-friendly transportation. The aim of the chapter is to identify the role of shared micromobility systems, particularly bicycle systems, in increasing access to railway transport. The analysis in the study is conducted using the example of the provincial bicycle system – "Rowerowe Łódzkie," focusing on its use for commuting to Łódzka Kolej Aglomeracyjna (ŁKA) railway stations. The chapter presents the results of a survey conducted among 116 respondents who are users of Łódzka Kolej Aglomeracyjna. The analyses indicate that although respondents positively evaluate the system in terms of its impact on access to ŁKA, they use it to a limited extent. The distribution of bicycle stations suggests that the improvement in this accessibility mainly applies to larger municipalities.